Pengaruh Pemahaman Pajak, Sistem Perpajakan dan Keadilan Pajak terhadap Persepsi Wajib Pajak Orang Pribadi Mengenai Penggelapan Pajak (Tax Evasion) : ( Studi Kasus pada Kpp Pratama Kota Kupang ) (Jurnal Kendali Akuntansi, 2025)
This study aims to determine the influence of tax understanding, the tax system, and tax fairness on individual taxpayers' perceptions of tax evasion. This research uses a survey method with a quantitative descriptive approach. The types of data used are primary and secondary data. Data collection was conducted through the distribution of questionnaires. The analytical technique used is multiple linear regression analysis. The results of this study show that, partially, tax understanding and tax fairness have an influence, while the tax system variable does not. Meanwhile, simultaneously, the variables of tax understanding, tax system, and tax fairness together influence individual taxpayers' perceptions of tax evasion.